2003
DOI: 10.1103/physrevb.67.205213
|View full text |Cite
|
Sign up to set email alerts
|

Impurity band in lithium-diffused and annealed GaAs: Conductivity and Hall effect measurements

Abstract: Originally n-type Si-doped GaAs turns p-type after Li indiffusion and consequent annealing at 200-600°C. Temperature-dependent conductivity and Hall effect measurements carried out in the temperature range 30-300 K reveal conduction via impurity bands made up of shallow acceptors in addition to the valence-band conduction. Li diffusion into GaAs reduces the free-carrier concentration which leads to electrical resistivity as high as 10 7 ⍀ cm. Annealing highly resistive samples at temperatures above 200°C signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…We found that the conductivity increased with increasing temperature; it seemed to indicate that the transport mechanism in the sample was by holes in valence band. The conductivity (σ ) from holes in valence band can be described by the following equation [10,11]: where A is a temperature-independent constant, E A is the acceptor activation energy, k is the Boltzmann constant and T is the thermodynamic temperature. The dash line in figure 2 is a fit to σ versus T data by equation (1).…”
Section: The Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the conductivity increased with increasing temperature; it seemed to indicate that the transport mechanism in the sample was by holes in valence band. The conductivity (σ ) from holes in valence band can be described by the following equation [10,11]: where A is a temperature-independent constant, E A is the acceptor activation energy, k is the Boltzmann constant and T is the thermodynamic temperature. The dash line in figure 2 is a fit to σ versus T data by equation (1).…”
Section: The Conductivitymentioning
confidence: 99%
“…The temperature dependence of conductivity was fitted by the mix of band and nearestneighbour hopping conduction mechanisms. In such a case, the relationship between the total conductivity and temperature can be expressed as [10,11] σ total = σ band + σ nn = A exp(−E A /kT ) + B exp(−E nn /kT ).…”
Section: The Conductivitymentioning
confidence: 99%
“…The black dashed lines present the isolines of different conductivity value, σ, which is defined as σ = nqμ . Here the values of carrier concentration, mobility, and conductivity are taken from literature. …”
mentioning
confidence: 99%